Development Of Creative Industry Eco-Print As an Effort to Improving The Quality and Productivity Business Business Hand Craft Shans's Craft in Medan - Dalimunthe, Doli Muhammad Jafar; Adika Fajar Putra; Hutagalung, Arif Qaedi; Sianipar, Aryanti Sariartha (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
With creativity, items that have no value and are often considered trash can be turned into a product with high economic value, for example leaves. Shanti Permatasari as a creative industry player for home handicrafts created by Shan's Craft uses leaves as raw materials to make various products using the Eco-print technique. Eco-print is a method of coloring and printing natural motifs on fabrics that utilizes leaves or flowers that grow in the yard as a substitute for chemical liquids and is also environmentally friendly. Coloring using natural elements will not cause environmental damage. The development of creative industries is needed to foster community creativity, especially during the current Covid-19 pandemic. Creative industries in the form of handicrafts get enough attention, especially as souvenirs and souvenirs. With the existing potential, the production of the Shan's Craft creation house in the form of handicrafts using the Eco-print technique needs to be supported to increase production and marketing more seriously. Although this business has promising opportunities, there are obstacles in the production process due to the limited space of the workshop which limits the space for movement, production, and even for displaying product displays. In terms of financial management, businesses still combine personal finance and business finance, there is no clear cash flow report on a regular basis. This causes the business to have no clear advantages/disadvantages and is relatively slow to develop. Through this service program, the implementation team offers solutions in the form of expansion and construction of product display rooms for promotional needs, creation of online media accounts as a means of digital promotion, and financial management training and simple bookkeeping of financial statements. The targeted outputs are increased production and sales of eco-print batik, maximum utilization of product display space in reaching the target market, and expanding the market through the use of online media such as social media and e-commerce.